Um modelo hÃbrido baseado em ontologias e RBC para a concepÃ§Ã£o de um ambiente de descoberta que proporcione a aprendizagem de conceitos na formaÃ§Ã£o de teorias por intermÃ©dio da metÃ¡fora de contos infantis - Pessôa Neto, Agnaldo Cavalcante de Albuquerque (2006)
The actual work shows a model of discovery learning in order to realize a discovery environment (PARAGUAÇU, 1997) to demonstrate to the apprentice students in science, the understanding of how the concepts that are used in the creation of scientific theories are related. The subject is reached with the idea that is possible to create scientific theories in scientific models (FRIGG; HARTMANN, 2006; RUDNER, 1969), and that these models can be used to help in such learning. However, with the availability of such models, instead of introducing scientific terms related to some scientific topics, it intends to use the metaphor of Fairy Tales, what means, the vocabulary use of terms where the apprentice can understand by intuition on how a scientific theory is elaborated. On the other hand, in order to create and formalize this scientific model it was created the idea that was proposed by MIDES Architecture MIDES (PARAGUAÃ‡U et al., 2003), which means the creation of a scientific model with the representation in XML (W3SCHOOLS, 2005b) in four views of knowledge: Hierarchy, Relational, Causal, and by Asking. So, the idea of this work is to show how the creation in XML is made, and to do so, it s necessary to make a review of the following subjects: learning environments; teaching based on cases; and some general aspects of a creation of a scientific theory, and about the creation of a theory like an axiomatic system, as well as to present the ideas for the elaboration of discovery learning models. When this review is done, we have the necessary knowledge to propose an architecture able to integrate two applications by the use of XML, that is, the first application is to a teacher s community that elaborate theories in scientific models using the metaphor of the Fairy Tales, and the second one, for students that desire to learn how the creation of a theory is made, by the use of models that were introduced by the teacher s community.